Equivalence between the boundary Harnack principle and the Carleson estimate - Aikawa, Hiroaki (MATHEMATICA SCANDINAVICA, 2008)
Both the boundary Harnack principle and the Carleson estimate describe the boundary behavior of positive harmonic functions vanishing on a portion of the boundary. These notions are inextricably related and have been obtained simultaneously for domains with specific geometrical conditions. The main aim of this paper is to show that the boundary Harnack principle and the Carleson estimate are equivalent for arbitrary domains.